2012
DOI: 10.1515/bmc-2012-0001
|View full text |Cite
|
Sign up to set email alerts
|

The role of hyperosmotic stress in inflammation and disease

Abstract: Hyperosmotic stress is an often overlooked process that potentially contributes to a number of human diseases. Whereas renal hyperosmolarity is a well-studied phenomenon, recent research provides evidence that many non-renal tissues routinely experience hyperosmotic stress that may contribute significantly to disease initiation and progression. Moreover, a growing body of evidence implicates hyperosmotic stress as a potent inflammatory stimulus by triggering proinflammatory cytokine release and inflammation. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
221
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 240 publications
(228 citation statements)
references
References 160 publications
(231 reference statements)
7
221
0
Order By: Relevance
“…Here, the authors found that betaine (trimethylglycine), a natural specific type of zwitterion, known to improve visual acuity, has antioxidant properties and inhibits pathological neovascularization of human retinal microvascular endothelial cells exposed to high glucose levels, by attenuating ROS production, and subsequently suppressing both the VEGF receptor (VEGFR)-2 signaling pathway and VEGF production [3]. Betaine was, here, reported to act on the hyperosmolar component of hyperglycemia [4], a biophysical mechanism known to contribute to the development of microvascular disease in diabetes [5][6][7]. Thus, betaine would act on one pathway leading from hyperglycemia to microangiopathy.…”
Section: Introductionmentioning
confidence: 99%
“…Here, the authors found that betaine (trimethylglycine), a natural specific type of zwitterion, known to improve visual acuity, has antioxidant properties and inhibits pathological neovascularization of human retinal microvascular endothelial cells exposed to high glucose levels, by attenuating ROS production, and subsequently suppressing both the VEGF receptor (VEGFR)-2 signaling pathway and VEGF production [3]. Betaine was, here, reported to act on the hyperosmolar component of hyperglycemia [4], a biophysical mechanism known to contribute to the development of microvascular disease in diabetes [5][6][7]. Thus, betaine would act on one pathway leading from hyperglycemia to microangiopathy.…”
Section: Introductionmentioning
confidence: 99%
“…1 Most organisms are exposed chronically or accidentally to high salinity environments and the ability to adapt to the availability of water is essential for life. In humans, many organs are exposed to water stress, due to water evaporation such as the skin, or through water osmosis into more concentrated aqueous environments due to physiological processes such as in kidneys, colon, and bladder.…”
Section: Introductionmentioning
confidence: 99%
“…Osmotic stress, associated with systemic infections 43 , is sensed and regulated by the infected host, via several mechanisms including the activation of nuclear factor of activated T cells 5 (NFAT5) 44 (Figure 2). The osmotic stress response regulated by this transcription factor acts in a cytoprotective manner in parenchyma cells 45 , conferring tissue damage control in the kidney during systemic polymicrobial infections 46 and likely in the heart during infection with coxsackievirus 47 in mice ( Figure 2). …”
mentioning
confidence: 99%